Approaches to Hysterectomy - Amarin, Zouhair O. (IntechOpen, 2015)
Hysterectomy is a very common type of surgery and can be a life-saving operation for some women with certain types of cancer or torrential uterine haemorrhage. It can also improve the quality of life for women who experience menometrorrhagia, uterine leiomyomata, endometriosis or uterine prolapse. However, before embarking on hysterectomy, it is important to be aware of and understand all the options available, medical or conservative surgical, as well as their risks and benefits. The most determinant factors for choosing one or another approach are uterine size, organ mobility, parity and previous pathology, in integration with best research evidence, clinical expertise and patient values and expectations. This book is intended for all specialties involved in health care for women.